2018
DOI: 10.3892/etm.2018.6440
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous renal artery stent implantation in the treatment of atherosclerotic renal artery stenosis

Abstract: We aimed to investigate the clinical curative effect of percutaneous renal artery stent implantation (PTRAS) in the treatment of atherosclerotic renal artery stenosis (ARAS), and to analyze the factors influencing the curative effect of PTRAS. A total of 230 patients with unilateral or bilateral renal artery stenosis were retrospectively analyzed. According to whether adverse cardiogenic or nephrogenic events occurred, 230 patients were divided into two groups to analyze the risk factors of adverse cardiogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
(21 reference statements)
0
7
1
Order By: Relevance
“…In our study, MACCE-RRT was observed in 49.5% of diabetic patients at follow-up, compared to general population where adverse outcomes were reported in 30% to 75% of patients undergoing PTA for ARAS [19,22,23,26]. However, meta-analysis of randomized and non-randomized studies showed the effect size of 0.55 to 2.35 for all-cause death and cardiovascular mortality, with no statistically significant differences between PTA and medical therapy alone [27].…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…In our study, MACCE-RRT was observed in 49.5% of diabetic patients at follow-up, compared to general population where adverse outcomes were reported in 30% to 75% of patients undergoing PTA for ARAS [19,22,23,26]. However, meta-analysis of randomized and non-randomized studies showed the effect size of 0.55 to 2.35 for all-cause death and cardiovascular mortality, with no statistically significant differences between PTA and medical therapy alone [27].…”
Section: Discussioncontrasting
confidence: 50%
“…Furthermore, results of the clinical series showed that revascularization of the stenotic lesion compared with medical therapy may be potentially associated with renal and cardiovascular prognosis improvement [10,21,22]. Thus, data gathered in this field strongly suggest individualized and personalized attitude as they are mostly ambiguous [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AUCi was one of the independent risk factors for RFD during 1 year of follow-up. Therefore, renal cortical blood perfusion is a useful supplement for clinicians to evaluate the degree of renal ischemia, judge the prognosis, and guide the treatment of RAS revascularization ( 18 ).…”
Section: Discussionmentioning
confidence: 99%